Acceptability of Treatments and Services for Individuals with Hoarding Behaviors - Rodriguez, Carolyn I. (J Obsessive Compuls Relat Disord, 2016)
OBJECTIVE: To explore the acceptability of currently available treatments and services for individuals who self-report hoarding behaviors. METHOD: Between 10/2013 and 8/2014, participants were invited to complete an online survey that provided them descriptions of eleven treatments and services for hoarding behaviors and asked them to evaluate their acceptability using quantitative (0 [not at all acceptable] -10 [completely acceptable]) Likert scale ratings. The a priori definition of acceptability for a given resource was an average Likert scale score of six or greater. Two well-validated self-report measures assessed hoarding symptom severity: the Saving Inventory-Revised and the Clutter Image Rating Scale. RESULTS: Two hundred and seventy two participants who self-reported having hoarding behaviors completed the questionnaire. Analyses focused on the 73% of responders (n=203) who reported clinically significant hoarding behaviors (i.e., Saving Inventory-Revised scores of ≥40). The three most acceptable treatments were individual cognitive behavioral therapy (6.2 ±3.1 on the Likert scale), professional organizing service (6.1 ±3.2), and use of a self-help book (6.0 ±3.0). CONCLUSION: In this sample of individuals with self-reported clinically significant hoarding behaviors (n=203), only 3 out of 11 treatments and services for hoarding were deemed acceptable using an a priori score. While needing replication, these findings indicate the need to design more acceptable treatments and services to engage clients and maximize treatment outcomes for hoarding disorder.